Social Media and Mass Empowerment: Towards a Theory of Digital Legitimacy - Greene, Amanda R. (Journal of moral philosophy, 2024)
Many people are concerned about the legitimacy of digital technology companies like Meta. In this paper we show that two existing models for characterizing power – sovereign power and structural power – are inadequate when it comes to digital technology companies. This is because they fail to accommodate something crucial: the uniquely empowering nature of digital power. Companies like Meta empower users to interact by providing them with versatile systems defined by minimalist permission structures. Drawing on Searle’s theory of institutions and Hart’s theory of law, we show how these permission structures facilitate the creation of new powers, as well as new institutions, through the emergence and recognition of new social norms. This means we must ask how entities that provide us with such versatile – and thus unsteerable – means of empowerment can come to be legitimate. We argue that a custodial framework for digital legitimacy can assign responsibility for the patterns of empowerment that are sustained by companies like Meta.